Implementation of Supply Chain Management in Supporting Vegetable Stock in Polewali Mandar Central - Nurfaldinianti; Dambe, Jumriani; Arfah, Salmawati (Program Studi Agribisnis Universitas Muhammadiyah Sinjai, 2025)
Vegetables are plants or parts of plants that are commonly consumed by Indonesian people as staple foods, appetite enhancers, or appetite stimulants This study aims to understand and describe the implementation of supply chain management in vegetable traders at Pekkabata Polewali Mandar Central Market. This study uses a qualitative approach with a case study method. The results of the study indicate that the implementation of supply chain management in Pekkabata Central Market has been running well. Good cooperation between traders and local farmers and distributors allows for the availability of stable and quality vegetables. Effective stock management also helps reduce the risk of loss due to damage or decreased quality of vegetables. Vegetable traders at Pekkabata Central Market also carry out strict supervision of vegetable quality and have the hope of having a comfortable and cool place to sell to maintain the quality of the vegetables sold. This study recommends improving communication and coordination between traders, farmers, and distributors, developing better information systems, and increasing awareness of the importance of vegetable quality for consumer health. The local government can also consider improving market facilities to improve the quality of vegetables sold.